Characterization of Detergent Purified Recombinant Rat Liver Monoamine Oxidase B Expressed in Pichia pastoris - Upadhyay, Anup K. (2008)
The high level expression and purification of rat monoamine oxidase B (rMAOB) in the methylotrophic yeast Pichia pastoris is reported. Nearly 100 mg of purified rMAOB is obtained from 130 grams (wet weight) of cells (0.5 liter of culture). The MALDI-TOF mass spectrum of the purified protein shows a single species with a molecular mass of 59.228 ± 0.064 kDa, which agrees with the calculated molecular weight of 59.172 kDa for the rMAOB protein sequence assuming one mole of covalent FAD per mole of the enzyme. Consistent with the MALDI-MS data, purified rMAOB shows a single band near 60 kDa in Coomassie stained SDS/PAGE gel as well as on Western blot analyses performed using antiseras raised against human MAOA and BSA conjugated FAD. A partial amino acid sequence of the purified protein is confirmed to be that of the wild type rMAOB by in-gel trypsin digestion and MALDI-TOF-MS analyses of the liberated peptide fragments. Steady state kinetic data show that purified rMAOB exhibits a K(m)(amine) of 176 ± 15 µM and a k(cat) of 497 ± 83 min(−1) for benzylamine oxidation, and a K(m) (O(2)) of 170 ± 10 µM. Kinetic parameters obtained for purified rMAOB are compared with those reported earlier for recombinant human liver MAOB expressed in Pichia pastoris.